QUALITY OF PRIMARY HEALTH SERVICES IN COASTAL SAMPANG: PATIENT AND HEALTH OFFICER PERSPECTIVES - Fery Gunawan , Moh.; Pramono, Sapto; Fatah , Zainal (International Journal of Multidisciplinary Reseach, 2026)
This study explores the quality of primary healthcare services in the coastal area of ​​Sampang, Madura, focusing on both patients' and healthcare providers' perspectives. The unique geographical, social, and cultural characteristics of the region present considerable challenges that impact service delivery. Key issues identified include limited accessibility due to geographic distance and inadequate transportation infrastructure, shortages of trained and competent health personnel, and insufficient medical facilities and logistical support. These factors contribute to delays in service provision, lower service quality, and decreased patient satisfaction. Additionally, communication barriers stemming from language differences and cultural diversity hinder effective interactions between healthcare providers and the community, affecting trust and adherence to medical advice. The strain on healthcare workers, who often face high workloads and limited professional development opportunities, further exacerbates service gaps. From the patient's viewpoint, barriers such as difficult access, unclear medical information, and cultural misalignment diminish perceived service quality and health outcomes. Meanwhile, healthcare providers struggle with resource constraints and logistical difficulties, especially under adverse weather conditions and challenging terrains. The study underscores the importance of a holistic, culturally sensitive approach to enhancing healthcare delivery in remote coastal regions. Recommendations include strengthening infrastructure, increasing workforce capacity, fostering culturally appropriate communication, and improving logistical systems. Policies should prioritize integrated strategies that address geographic, social, and resource-related barriers to ensure equitable and high-quality primary healthcare services for coastal communities. Overall, addressing these multifaceted challenges is essential for improving health outcomes and achieving universal health coverage in underserved coastal areas.